(untitled) (Journal of Statistical Research, 2024)
The purpose of carrying out this study was to explore the trends and inter-linkages between CO2 emission and RE share of total energy between 1990 and 2015. The United Nations’ Sustainable Development Goal 7 is to ensure access to affordable, reliable, sustainable, and modern energy for all. With these targets in mind, we have tried to answer questions like how has the global RE share of total energy changed over time, does the pattern of RE change over time affect CO2 emissions, and has access to clean energy changed significantly over time? The findings of this study has established that there is a general increasing trend in RE and that is associated with diminished trend in CO2. Looking at the access to clean energy between rural and urban sectors and they presented starkly different time trend with almost twice as large a percentage of population with access to clean energy in the urban areas than the rural. Journal of Statistical Research 2024, Vol. 58, No. 1, pp. 221-242.